Unsettling the Columbian Exchange: Review of The Tame and the Wild: People and Animals after 1492 by Marcy Norton (2024) - Guest, Kristen (Humanimalia, 2024)
Review of:Marcy Norton, The Tame and the Wild: People and Animals after 1492. Cambridge, MA: Harvard University Press, 2024. 448 pp. $37.50 (hb). ISBN: 9780674737525.